2010
DOI: 10.1016/j.wneu.2010.02.046
|View full text |Cite
|
Sign up to set email alerts
|

Action Africa!

Abstract: In Sub-Saharan Africa because of the prevailing economy, the equipping of neurological and neurosurgical services, as well the training of younger colleagues remains a recurrent problem. Therefore, all currently available resources ought to be mobilized and put together to obtain very rapid, short-term results. This is not a dream. The forces of the improvement of development lie in our hands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Cubo et al [ 33 ] reported that a lack of imaging facilities impaired their ability to differentiate secondary Parkinsonism from idiopathic PD among the patients they were evaluating in Cameroon. Dechambenoit et al [ 41 ], in his paper “Action Africa,” described a lack of equipment and outdated operating theaters, with an absence of instruments for microsurgery and microscopes. He further stated that where neurosurgery institutes were available, they were inaccessible to 90% of the population due to a lack of health insurance systems.…”
Section: Resultsmentioning
confidence: 99%
“…Cubo et al [ 33 ] reported that a lack of imaging facilities impaired their ability to differentiate secondary Parkinsonism from idiopathic PD among the patients they were evaluating in Cameroon. Dechambenoit et al [ 41 ], in his paper “Action Africa,” described a lack of equipment and outdated operating theaters, with an absence of instruments for microsurgery and microscopes. He further stated that where neurosurgery institutes were available, they were inaccessible to 90% of the population due to a lack of health insurance systems.…”
Section: Resultsmentioning
confidence: 99%
“…A recent estimate put the ratio of neurosurgeons in Africa to population at 1 neurosurgeon: 4,000,000 people. [5] This low ratio has made neurosurgical services unavailable to a large section of the population. The problem of African neurosurgery has been the focus of several recent publications.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of African neurosurgery has been the focus of several recent publications. [56789] The outlook in Nigeria is even worse with about 27 neurosurgeons serving an estimated population of 170 million (ratio of 1:6.3 million). The African neurosurgeons are, almost exclusively, in urban centers.…”
Section: Introductionmentioning
confidence: 99%
“…IBRO African Centres for Advanced Training in Neuroscience have been established in Morocco and South Africa. WFNS-recognized Centres of Excellence for training neurosurgeons have been established in Nigeria, Ivory Coast, Senegal, Kenya, Zimbabwe and South Africa (Dechambenoit, 2010 ).…”
Section: Training In Neuroscience In Africamentioning
confidence: 99%